Heller, Anne C. (2021). Hannah Arendt. Una vida en tiempos de oscuridad. Trad. A. Nuño, Madrid: Alfabeto, 186 pps. - Merino Córdoba, Sacramento (Differenz. Revista internacional de estudios heideggerianos y sus derivas contemporáneas, 2022)
Biography of one of the great thinkers of the 20th century. Through the fundamental events in Arendt's life, Anne C. Heller shows us the pillars of Hanna Arendt's profoundly courageous thought. He unravels the reason for his identification with the term "conscious pariah" and conveys the power and current validity of his analysis of the banality of evil.